Pajak Karbon dan Dilema Pembangunan Ekonomi Indonesia: Pembelajaran dari Negara Lain - Syaikha Aulia; Julian Aldrin Pasha (Jurnal Syntax Admiration, 2024)
Indonesia issued a regulation on carbon tax through article 13 of Law No. 7 on the Harmonization of Tax Regulations (HPP) in 2021 following the number of countries that have implemented carbon pricing mechanisms in facing the challenge of climate change. In addition to the policy formulation process full of pros and cons, the policy was actually postponed until 2015. Learning from the experience of other countries, the implementation of carbon taxes does not always succeed in reducing emissions or household budgets. The facts show that economic development and environmental control often do not occur at the same time. Additional rules, government commitment and cooperation from every relevant stakeholder are needed as well as supervision from the community in the implementation of article 13 of the HPP Law.